The Methodoloy of Ibn Hazm in comparative religion with special reference to his master piece Al-fadl fi Al-Milal Wa Al-Ahw’ Ws Al-Nihal - Shehu, Fatmir Mehdi (2011)
This paper attempts to study the methodology of classical scholar of ‘Ilm al-KalÉm, Ibn ×azm, in comparative religion with special reference to his master piece “Al-Fal f al-Milal wa al-Ahw’ wa al-Nial.” It will provide extensive exposition of Ibn ×azm’s contribution in the development of the science of comparative religion. The focus of this research will be on the study of: (1) bibliography of Ibn Hazm and his writings related to comparative religion; and, (2) the methodology used by him in his study of Christianity with examples. The findings of this research hope to assist the Muslim scholars of 21st century in comparative religion to develop a better methodology in their study of other religions, which leads to mutual respect and better understanding of others.